Respuesta :

Answer:

[tex]\textsf{E.} \quad y\:dy=xe^x\:dx[/tex]

Step-by-step explanation:

Given equation:

[tex]ye^{-x}\dfrac{dy}{dx}=x[/tex]

Divide both sides by [tex]e^{-x}[/tex]:

[tex]\implies \dfrac{ye^{-x}}{e^{-x}}\:\dfrac{dy}{dx}=\dfrac{x}{e^{-x}}[/tex]

[tex]\implies y\:\dfrac{dy}{dx}=\dfrac{x}{e^{-x}}[/tex]

Multiply both sides by [tex]dx[/tex] :

[tex]\implies y\:\dfrac{dy}{dx}\cdot dx=\dfrac{x}{e^{-x}}\cdot dx[/tex]

[tex]\implies y\:dy=\dfrac{x}{e^{-x}}\:dx[/tex]

[tex]\textsf{Apply exponent rule} \quad \dfrac{1}{a^{-n}}=a^n:[/tex]

[tex]\implies y\:dy=xe^x\:dx[/tex]

Answer: E

Step-by-step explanation:

[tex]ye^{-x} \frac{dy}{dx}=x\\\\y \frac{dy}{dx}=xe^{x} \\ \\ \boxed{y dy=xe^{x} dx}[/tex]

ACCESS MORE